An Investigation of the Effect of Devaluation of The Currency on Balance of Payments (To Examine Marshal Lerner Condition in Iran) - Farhad Dejpasand; Hossein Goudarzi (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2009)
Applied study about developing countries indicates real devaluation of the currency has different effect on balance of payments. Devaluation of the currency can improve balance of payment if the exchange market was in the relative stability and monetary and fiscal policy was also specified and not expansionary. Exchange market stationary examines by Marshal Lerner condition. Marshal Lerner condition states that if absolute sum of demand and supply elasticity of exchange rate is greater than one exchange market is stable and increasing exchange rate or devaluation of the currency can improve the balance of payments. This study examines Marshal Lerner condition in Iran by Time series and panel data model. The result of this empirical examine suggests that the Marshal Lerner condition